RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN STOK BAHAN BAKU BERBASIS WEB MENGGUNAKAN METODE PROTOTYPING - Lubis, Ahmad Faiz; Yusar, Muhammad Rajib; Wijaya, Dedi Sukma; Nuaridito, Muhammad Fahri; Sharyanto, Sharyanto; Prambodo, Yoga Listi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The raw material stock management process at PT. Kenari Djaja Prima was previously conducted manually, often leading to recording errors and delays in material procurement. This study aims to design and develop a web-based inventory information system to improve the accuracy and efficiency of stock recording, monitoring, and reporting. The research applies the prototyping method with a descriptive qualitative approach, consisting of requirement analysis, UML-based design, implementation using PHP and MySQL, and evaluation through black-box testing. Preliminary results show that the developed system performs according to its intended functions and assists the purchasing and warehouse departments in managing stock data more effectively. The main contribution of this study is to provide an integrated digital solution for enhancing raw material inventory control in manufacturing environments.